Ads over “FreeFi” - Mammadov, Rovshan (ADA University, 2019)
Advanced technology has become a main part of our life recent years. The majority of population uses mobile devices in daily activities, they do a part of their jobs, communicate with each other, do online shopping through them and etc. The Internet and social networks have also become an integral part of our lives and its popularity growing. The idea of this business plan is to take an opportunity of the advanced technologies and benefit from the Internet in setting a business in the country. We are going to provide advertisement services to population in free Wi-Fi zones which is expanding very fast since almost all public places are becoming free Wi-Fi areas. These places are becoming indispensable for marketing and advertising. On the contrary, other advertisement channels such as TV, radio, newspapers etc. lose their popularity gradually. In the first chapter of the project, we provided background of the industry, analyzed current market situation and opportunities. The way how we are going to implement this business is also reviewed in this piece of the project. Covering Baku and a part of Absheron peninsula, not having enough experiences in the planned sector, market size and some other factors are listed as limitations for this business. However, customer segmentation will be core value and main driver of success of this project. We have conducted survey among roughly 500 people in order to study the market potential, consumers expectations, industry and market growth potentials. All study and analysis support the planned business feasibility and encourage BP owner to start this business. In the second section, I explained the planned company description in terms of vision, mission and values that we are going to differentiate the business. There are not any competitors in the local market which could be considered as one of the main advantages for this startup. Service details are described in this chapter and potential key partners are also identified. In fact, on the one hand, any advertisers could be the potential customers for this business. On the other hand, business locations are also our potential partners as we will provide them valuable information about their customers which could be used to increase loyalty and expand current businesses via target-oriented campaigns. Survey results show that the considerable part of consumers is not interested in following ads through existing advertisement channels and in most cases, ads are skipped by them. Short and long run growth strategy of this business was given in this section. I tried to take into consideration ethical and legal issues of this business while preparing mentioned business plan. In the third chapter, industry and market analysis are given. Different theories such as Porter’s five forces, SWOT analysis, PEST analysis and business model CANVAS are studied in this section. I also tried to detect customer expectations from this industry and market which is considerably important for this kind of businesses. Analysis show that there is significant space for the market growth which could be considered as “blue ocean” for the country. In addition, prepared strategic roadmap for 2016-2025 years which was signed by the president of Azerbaijan Republic which provides wider opportunities for startups, especially businesses related to IT and telecommunication. Statistics confirm that Azerbaijan is one of the faster developing countries in the world since total GDP and GDP per capita have been rising for the last several years. This indicator could be considered as one of the positive factors to attract foreign investors to the country. In the next section, I explained details of the organization, human resource strategy and the way of managing the company etc. We assume that there will be five employees in the company for the initial stage. Sales and marketing specialists, IT operation engineer and software developer will support company operation under general manager supervision. We understand that better working environment is one of the essential factors of the business success. I explained my own vision for this regard – how the working environment is going to be, what will be our operation plan, how we will provide services to customers, working hours of employees and so on. In the fifth section, we defined the brand for planned business and its slogan. These attributes are also important as the first impression about the company is created based on them. We tried to make logo of the company simple, but impressive and understandable. Slogan also was chosen short with great meanings behind. Our plan is to start with 5 locations of restaurant “Mado” placed in different points of the city and one of the biggest shopping centers of Baku. We reviewed required equipment to provide services in the planned areas and clarified it with owners or managers of those locations. It is defined that restaurants have own devices and provides Wi-Fi to clients currently while shopping centers do not have centralized service which means we will deliver modems and switch to them in order to secure Wi-Fi connections to users. Chapter six is one of the crucial parts of the business plan which is related to financial analysis and forecasts. It is significantly important in terms of funding, attracting investors, feasibility of the business from financial perspective and finally, to make a conclusion if it makes sense to start this business in general or not. I made detailed analysis of startup cost for this business, explained fixed and stepped (variable) costs, revenue, financial statements and so on. Expected startup cost of this business will cost approximately 65.800 AZN. We are going to cover this cost with shareholders equity and bank loan. Projected total revenue for the five years of operation will be 2.353.600 AZN while total expenses will be roughly 1.600.000 which means this business is feasible in terms of financial projection as well. Finally, in the seventh section I dealt with expected risks and exit strategy for the business. It is undeniable fact that every business has threat of bankruptcy in some degree. It is valuable if business owners have “Plan B” for emergency situations. Exit strategy is necessary not only for business owners, but also for investors in order to show the ways of returning of investments in case of bankruptcy or exit from the business at some points. We developed two exit strategies for the company. The first option will be going for Management buyout with potential competitor in the market and the second choice is to sell the company.
Keywords: Business; Broadband communication systems.; Broadband communication systems -- Azerbaijan.; Telecommunication -- Technological innovations.; Telecommunication -- Technological innovations -- Azerbaijan.; Wireless Internet.; Wireless Internet -- Azerbaijan.; Wireless communication systems.; Wireless communication systems -- Azerbaijan.